The long-term effects of long terms: Compulsory schooling reforms in Sweden - Martin Fischer; Martin Karlsson; Therese Nilsson; Nina Schwarz (Research Institute of Industrial Economics (IFN), 2018)
We evaluate the impact on earnings, pensions, and further labor market outcomes of two parallel educational reforms increasing instructional time in Swedish primary school. The reforms extended the annual term length and compulsory schooling by comparable amounts. We find striking differences in the effects of the two reforms: at 5%, the returns to the term length extension were at least half as high as OLS returns to education and bene ted broad ranges of the population. The compulsory schooling extension had small (2%) albeit significant effects, which were possibly driven by an increase in post-compulsory schooling. Both reforms led to increased sorting into occupations with heavy reliance on basic skills.
Keywords: J24; J31; I28; 330; Educational reforms; Compulsory schooling; Term length; Returns to Education